Slides to Philosophy 167: Class 2 -- 16th Century Astronomy: Copernicus and Tycho Brahe -- Part 9. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 2, Part 9.